Pengujian Unjuk Kerja dan Pengukuran Parameter Motor Induksi Satu Fasa - Susanto, Erwin, Agus Ulinuha, ST., MT., Ph.D (2017)
Utilization of an induction motor as the main driver requires an adjustment to the load so that the appropriate application and no interference. Therefore it was examined by means of testing without a load, with load testing and testing by means of rotor withheld (blocked) until the rotational speed of 0. In this test the input voltage is adjusted gradually from 75 V, 125 V, 175 V and 220 V. in the first test with the testing without a load voltage of 75 V to 220 V there is an increase of motor current, motor power and motor speed (rpm). At a voltage of 220 V without a load test, the obtained data is a maximum of 0.85 Ampere current, power 162 Watt, while the rotational speed 2940 rpm. While the influence of the rotational speed of the motor torque in the second test with the same input voltage starting voltage of 75 V, and 10 Watt light load motor speed 1591 rpm while the torque is 0,130 Nm. However, in determining motor torque, motor power can affect a large torque of the motor. For the maximum torque of the motor is approximately 0,529 Nm. Later testing by means of a rotor on hold until rpm 0 for 3 to 4 seconds to determine the maximum current and maximum power corresponding input voltage starting from 75 V up to a maximum voltage of 220 V.